The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1084/jem.179.6.1867
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated virus 2-mediated high efficiency gene transfer into immature and mature subsets of hematopoietic progenitor cells in human umbilical cord blood.

Abstract: StlmmlryRecombinant adeno-assodated virus 2 (AAV) virions were constructed containing a gene for resistance to neomycin (neoa), under the control of either the herpesvirus thymidine kinase (TK) gene promoter (vTK-Neo), or the human parvovirus B19 p6 promoter (vB19-Neo), as well as those containing an upstream erythroid cell-specific enhancer (HS-2) from the locus control region of the human fl-globin gene cluster (vHS2-TK-Neo; vHS2-B19-Neo). These recombinant virions were used to infect either low density or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(64 citation statements)
references
References 59 publications
2
61
0
1
Order By: Relevance
“…29,30 Briefly, human embryonic kidney 293 cells, grown to 60% confluence in a 15-cm dish, were co-transfected with 12.5 g of helper plasmid pKS rep/cap and 12.5 g of vector plasmid pCMVAAV-cm-Epo by the calcium phosphate co-precipitation method. The precipitate was left on the cells for 8 h and the medium was replaced with IMDM + 10% FBS containing adenovirus type 5 dl312 at a multiplicity of infection (MOI) of 2.…”
Section: Methodsmentioning
confidence: 99%
“…29,30 Briefly, human embryonic kidney 293 cells, grown to 60% confluence in a 15-cm dish, were co-transfected with 12.5 g of helper plasmid pKS rep/cap and 12.5 g of vector plasmid pCMVAAV-cm-Epo by the calcium phosphate co-precipitation method. The precipitate was left on the cells for 8 h and the medium was replaced with IMDM + 10% FBS containing adenovirus type 5 dl312 at a multiplicity of infection (MOI) of 2.…”
Section: Methodsmentioning
confidence: 99%
“…We observed a similar trend in K562 cells 17 where very high MOIs were required for stable integration of the rAAV transgene and these findings have been independently confirmed by others. 26 Some investigators however, report efficient and long-term transduction of human 9,14,28,36,55 and murine hematopoietic progenitors 20 using relatively low rAAV MOIs. Even allowing for variGene Therapy ation in vector design and reporter genes there are several notable differences in the way these studies were performed.…”
Section: The Induced and The Uninduced Cells Were Then Transferred mentioning
confidence: 99%
“…8 Early studies suggested that rAAV vectors could transduce primitive human hematopoietic cells. [9][10][11][12][13][14] However, these studies were performed with crude vector preparations composed of lysate derived from producer cells, which had been infected with adenovirus and co-transfected with the vector plasmid and a packaging plasmid encoding the AAV proteins. Such preparations contain wild-type AAV, which arises by virtue of non-homologous recombination between the vector and packaging plasmids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 AAV infects and integrates into the chromosomes of a wide range of host cells. [5][6][7][8] Recombinant AAV (rAAV) is generated from AAVbased plasmids in which all of the genomic DNA, except for the ITR, has been replaced by the desired gene therapy construct. 5,9 Recombinant AAV can also integrate into the genome of a wide range of host cells including lymphoid cells, 5,[10][11][12] and does not replicate and cannot be rescued upon superinfection with adenovirus unless wild-type AAV is also present.…”
Section: Introductionmentioning
confidence: 99%